CONTENTS OF HEAVY METALS Hg, Cd, Pb, Cr IN BIVALVES FROM ESTUARIES IN CENTRAL VIETNAM - Khanh, Nguyen Van; Vinh, Tran Duy; Nhi, Le Ha Yen (Vietnam Journal of Marine Science and Technology, 2014)
Heavy metal contents in Corbicula subsulcata, Meretrix meretrix, Perna viridis and Saccostrea sp. from estuaries in Central Vietnam, including Thuan An, Han river, Dai, Sa Can, Song Kon - Thi Nai lagoon were higher than maximum permissible limit, compared to QCVN 8:2-2011/BYT for Hg, Cd and Pb and Metallic Contamination Regulations of the Public Health and Municipal Services Ordinance (PHMSO), Laws of Hong Kong for Cr. Particularly, Hg content in Corbicula subsulcata and Saccostrea sp. from Thuan An in August 2012 was higher than maximum permissible limit. The excess of critical value of Cd content in bivalves was also recorded at some research sites, especially in Dai and Sa Can estuaries. Noteworthily, average Pb contents in most bivalves from the estuaries exceeded the maximum permissible limit recommended by Vietnamese Ministry of Health, the number of samples that were 1.5 to 2.8 times higher than the maximum permissible limit accounted for 65%. Regarding to Cr, the contamination was also found in Meretrix metrix, Perna viridis and Saccostrea sp. from Han estuary and in Saccostrea sp. and Corbicula subsulcata from Sa Can in March 2013, compared to PHMSO. The accumulations of heavy metals (Hg, Cd and Cr) were significantly different among the estuaries, the species and sampling time while small differences were found in case of Pb.